A Study on Cash and Cash Management: Principles and functions of cash and cash management in business enterprises (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Cash, is always considered as the blood stream for every business as it gives vitality and strength”. In the literal sense, cash management refers to management of cash so as to achieve the business aims. In such a context, the aims of a business can be integrated so as to bring about consistency between highest possible profitability and liquidity of the firm .In the recent times most of the business concerns are facing a severe problem due to the non availability and increased cost of procuring and holding of money. This study aims at understanding the concepts of cash and cash management along with its principles ad functions for better working of the financial management of a business enterprise.